Development of E-Modules With Problem-Based Learning (PBL) to Increase Economic Learning Outcomes (Universitas Negeri Semarang, 2022)
The aim is to find out how valid, practical, and effective e-module development with the Kvisoft Flipbook Maker application is used in economics learning to improve learning outcomes for high school students. This development research resulted in a product in the form of e-module teaching materials with the Kvisoft Flipbook Maker application, which was developed with a 4-D model into 4 stages, namely defining, designing, developing, and disseminating. Based on the validation by the validator used for the very good e-module and the reliability of all validators in the reliable category, so that the e-module is feasible to use in learning. The form of innovation in learning resources and learning approaches gives a positive response to students, where the results of student responses to e-modules are obtained from all aspects of economic e-modules with the Kvisoft Flipbook Maker application very well. Different learning outcomes between the control class and the experimental class, meaning that the e-module product proved to be effectively applied in economics learning, where the increase in student learning outcomes in the experimental class in the learning outcome was in the medium category.